2018
DOI: 10.1007/978-3-319-91800-6_15
|View full text |Cite
|
Sign up to set email alerts
|

Towards Collaborative Data Analysis with Diverse Crowds – A Design Science Approach

Abstract: The last years have witnessed an increasing shortage of data experts capable of analyzing the omnipresent data and producing meaningful insights. Furthermore, some data scientists mention data preprocessing to take up to 80% of the whole project time. This paper proposes a method for collaborative data analysis that involves a crowd without data analysis expertise. Orchestrated by an expert, the team of novices conducts data analysis through iterative refinement of results up to its successful completion. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Research has found that peer production group members use other's history of project activity to form impressions of other's expertise (Marlow, Dabbish, & Herbsleb, 2013). An expert leader in a crowd worker team can also be helpful in leading non-experts to successfully accomplish data analysis tasks (Feldman, Anastasiu, & Bernstein, 2018). Finally, collective intelligence systems can help organizations to create optimal teams from crowds to fit specific organizational needs (Malone et al, 2010).…”
Section: Technology As Creation Mediummentioning
confidence: 99%
“…Research has found that peer production group members use other's history of project activity to form impressions of other's expertise (Marlow, Dabbish, & Herbsleb, 2013). An expert leader in a crowd worker team can also be helpful in leading non-experts to successfully accomplish data analysis tasks (Feldman, Anastasiu, & Bernstein, 2018). Finally, collective intelligence systems can help organizations to create optimal teams from crowds to fit specific organizational needs (Malone et al, 2010).…”
Section: Technology As Creation Mediummentioning
confidence: 99%